Youth Employment in Uzbekistan : Opportunities and Challenges - Honorati, Maddalena (World Bank, Washington, DC, 2021)
The objective of the report is to assess and find potential solutions to the challenge’s youth face when transitioning from school to work with a focus on labor market ‘supply side’ reforms that are relevant to improve the employability of youth. We recognize that rural and urban investment climates, regulatory frameworks, taxation systems, overall macro‐economic frameworks, and human capital (education and training policy, basic health) are prerequisites for many interventions on the demand side of the labor market to be successful. The report provides a holistic assessment, including both demand and supply‐side constraints, triangulating findings from available qualitative and quantitative data on youth and employers. It inevitably documents an extensive set of issues. However, it does not aim to assess the broader investment climate and macro context or all firm‐level constraints to job creation as a full job diagnostic would do. The lack of jobs and slow labor demand are found to be major constraints to youth employment, but macro and structural constraints to job creation are not assessed in the report in depth. The scope of the policy recommendations put forth focus on labor market reforms that could improve the employability of youth and are meant to complement recommendations on a broader set of macro and business environment reforms aimed at enabling private firms to start up, grow, and create jobs. Until major constraints to labor demand are addressed and job creation picks up, the recommendations presented in the report will remain necessary but will not be sufficient to address the youth employment challenge.